Soekarno's Visit to Padangsidimpuan in 1948: Historical Significance, Political Mobilization, and Local Support during the Indonesian Revolution - Kurnia Syahputra; Albert Waruwu; Ridho Affandi Panjaitan; Dea Puspita Sari; Mita Dina Prastiwi Hutahuruk; Rendi Rianto Simarmata (Warisan: Journal of History and Cultural Heritage, 2026)
This study examines Soekarno's visit to Padangsidimpuan on 12 June 1948 within the political context of Indonesia's struggle to defend its independence following the Renville Agreement. Although the visit represented an important episode during the Indonesian Revolution, its historical significance at the local level has received limited scholarly attention. This study reconstructs the chronology of the visit, analyzes its role in political mobilization, and examines the forms of local support that emerged in response to Soekarno's presence. The research employs the historical method, consisting of heuristics, source criticism, interpretation, and historiography, by analyzing contemporary newspapers, photographic documentation, archival records, and interview data through systematic source corroboration. The findings indicate that the visit served not only as a symbolic political event but also as a strategic instrument for reinforcing national legitimacy, mobilizing public participation, and strengthening local support for the Republic during a critical stage of the Indonesian Revolution. Public enthusiasm, despite adverse weather conditions, and the presentation of ulos and buffaloes in the Angkola-Mandailing tradition, reflected the integration of local cultural expressions into the broader national struggle. This study contributes to local history by demonstrating how the historical significance of Soekarno's visit extended beyond ceremonial purposes, functioning as a mechanism of political mobilization that strengthened state–society relations and reinforced collective support for the Indonesian Republic.